Evaluating the unusual histological aspects of granuloma annulare: A study of 30 cases - Debajyoti Chatterjee; Manveen Kaur; R. P. S Punia; Mala Bhalla; Uma Handa (Wolters Kluwer Medknow Publications, 2018)
Background: Granuloma annulare (GA) is an uncommon dermatologic disorder that presents as annular, skin-colored to erythematous plaques. Histopathologically, it is characterized by palisaded histiocytic granulomas. A definitive diagnosis of GA is based on clinicopathologic correlation. Objective: The aim of this study was to study the histomorphologic spectrum of GA. Materials and Methods: A total of 30 cases reported as GA over 6 years (2012-2017) were retrieved. The detailed clinical profile and histomorphologic findings on the skin biospies were reviewed. Results: Majority of the cases (40%) presented in the 6th decade of life with a mean age of 48.3 ± 16.5 years and with a female predominance (77%). The lesions were localized in 22 cases (73%). Asymptomatic to erythematous, annular plaques was the most frequent presentation (60%). GA was not suspected clinically in two cases. Histopathologically, interstitial pattern of infiltrate was most common (44%), whereas granuloma formation and palisaded histiocytes were seen in 4 (13%) and 3 cases (10%), respectively. A mixed pattern was observed in 10 (33%) cases. Collagen degeneration was universal finding (100%) and presence of dermal mucin was noted in 24 cases (80%), both of which were important clues to the diagnosis of GA. Additional features such as presence of plasma cells, eosinophils, and vasculitis were noted in 10 (33%), 6 (20%), and 6 (20%) cases, respectively. Conclusion: The diagnosis of GA may be challenging owing to its diverse morphology. Acquaintance with the varied histomorphology of GA is of utmost importance to render a correct diagnosis and understand the pathogenesis.